Antitumor Activity of Bioactive Compounds from Rapana venosa against Human Breast Cell Lines - Maria Petrova; Zlatina Vlahova; Maria Schröder; Jordana Todorova; Alexander Tzintzarov; Anastas Gospodinov; Lyudmila Velkova; Dimitar Kaynarov; Aleksandar Dolashki; Pavlina Dolashka; Iva Ugrinova (MDPI AG, 2023)
This study is the first report describing the promising antitumor activity of biologically active compounds isolated from the hemolymph of marine snail Rapana venosa-a fraction with Mw between 50 and 100 kDa and two structural subunits (RvH1 and RvH2), tested on a panel of human breast cell lines-six lines of different molecular subtypes of breast cancer MDA-MB-231, MDA-MB-468, BT-474, BT-549, SK-BR-3, and MCF-7 and the non-cancerous MCF-10A. The fraction with Mw 50-100 kDa (HRv 50-100) showed good antitumor activity manifested by a significant decrease in cell viability, altered morphology, autophagy, and p53 activation in treated cancer cells. An apparent synergistic effect was observed for the combination of HRv 50-100 with cis-platin for all tested cell lines. The combination of HRv 50-100 with cisplatin and/or tamoxifen is three times more effective compared to treatment with classical chemotherapeutics alone. The main proteins in the active fraction, with Mw at ~50 kDa, ~65 kDa, ~100 kDa, were identified by MALDI-MS, MS/MS analyses, and bioinformatics. Homology was established with known proteins with antitumor potential detected in different mollusc species: peroxidase-like protein, glycoproteins Aplysianin A, L-amino acid oxidase (LAAO), and the functional unit with Mw 50 kDa of RvH. Our study reveals new perspectives for application of HRv 50-100 as an antitumor agent used alone or as a booster in combination with different chemotherapies.